The Characteristics of Good Language Learners in Indonesia EFL Context - Atmowardoyo, Haryanto; Sakkir, Geminastiti; Sakkir, Rini Isnaeni (PT ARRUS Intelektual Indonesia, 2023)
This research aims to see and identify the characteristics of good language learners according to English language education students, at the Faculty of Languages and Literature, Makassar State University in 2023. The subjects of this research were fourth-semester students of the English Education Study Program, Department of English, because in that semester there were Learning and Teaching courses. This research wants to see what the student's language learning model are students in the fourth semester who took this course in 5 classes consisted of 210 students. However, this research was only carried out in 2 (two) classes, namely classes D and E with a total of 82 students. This research uses a qualitative approach, namely Qualitative Descriptive research. The results of this research show that Characteristics of good language learners (Good Language Learners) according to students include: Continuously practicing to hone their abilities/consistent/enthusiastic/patient/disciplined/diligent; Utilizing technology; Self-confident; Choosing a suitable and comfortable/adaptable environment; Adjustment; Motivation to learn/enthusiasm; Risk Taker; Self-habituation; Adapting the right learning style/strategy/method; Know the concept of language skills and language elements; Not easily give up; Have a Growth Mindset; Implementation of knowledge/ application/ practice/ active/ brave; Not afraid of being wrong; Search for solutions; Self-evaluation/self-reflection; High curiosity; Communication; Having a loud and loud voice; Know at least 3 languages; Creative; Use good/friendly/humble/polite/attitude language; Open to new cultures/adaptations; High awareness (Awareness); Long term commitment; Role models; Professional; Smart; Increase vocabulary; and read diligently.